Mg-Dopant Effects on Band Structures of Zn-Based Hydroxyapatites: A Theoretical Study - Bulut, Niyazi; Kaygili, Omer; Hssain, Ala Hamd; Dorozhkin, Sergey V.; Abdelghani, Benahmed; Orek, Cahit; Kareem, Rebaz Obaid (Springer Int Publ Ag, 2023)
The band structures of Zn-based hydroxyapatites co-doped with Mg at varying amounts from 0 to 2.0 at. % have been investigated theoretically in more detail. The calculations were done to obtain the band structure, density of states, and band gap for all the modeled structures to study their electronic properties. It was seen that the co-doping has an effect on the structural and electronic properties of all the as-investigated structures. The bandgap energy for all samples in each group was found to be reduced gradually with varying doping rates of Mg into Zn-doped HAp. The band gap decreased from 4.54 to 3.84 eV for samples of 0.4Zn-0.4 Mg-HAp and 2.0Zn-0.4 Mg-HAp with the same amount of Mg, respectively, as a result of increasing the doping levels of Zn from 0.4 to 2.0 at.%. The lattice parameters, unit cell volume, and density decrease with increase in doping of Zn-containing HAp and in addition of second dopant Mg at varying amounts 0.4, 0.8, 1.2, 1.6, and 2.0 at. % in all of the modeled sample group. Furthermore, it is observed that the declining values of the aforementioned parameters are significantly impacted by the increasing Zn doping rates.
Keywords: Hydroxyapatite; Density functional theory; Band gap